The association of α4β7 expression with HIV acquisition and disease progression in people who inject drugs and men who have sex with men: Case control studies - Martin, Alyssa R.; Patel, Eshan U.; Kirby, Charles; Astemborski, Jacquie; Kirk, Gregory D.; Mehta, Shruti H.; Marshall, Kyle; Janes, Holly; Clayton, Ashley; Corey, Lawrence; Hammer, Scott M.; Sobieszczyk, Magdalena E.; et al. (EBioMedicine, 2020)
α4β7 is a gut-homing integrin heterodimer that can act as a non-essential binding molecule for HIV. A previous study in heterosexual African women found that individuals with higher proportions of α4β7 expressing CD4+ T cells were more likely to become infected with HIV, as well as present with faster disease progression. It is unknown if this phenomenon is also observed in men who have sex with men (MSM) or people who inject drugs (PWID). MSM and transgender women who seroconverted as part of the HVTN 505 HIV vaccine trial and PWID who seroconverted during the ALIVE cohort study were selected as cases and matched to HIV-uninfected controls from the same studies (1:1 and 1:3, respectively). Pre-seroconversion PBMC samples from cases and controls in both studies were examined by flow cytometry to measure levels of α4β7 expression on CD4+ T cells. Multivariable conditional logistic regression was used to compare α4β7 expression levels between cases and controls. A Kaplan-Meier curve was used to examine the association of α4β7 expression pre-seroconversion with HIV disease progression. In MSM and transgender women (n = 103 cases, 103 controls), there was no statistically significant difference in the levels of α4β7 expression on CD4+ T cells between cases and controls (adjusted odds ratio [adjOR] =1.10, 95% confidence interval [CI]=0.94,1.29; p = 0.246). Interestingly, in PWID (n = 49 cases, 143 controls), cases had significantly lower levels of α4β7 expression compared to their matched controls (adjOR = 0.80, 95% CI = 0.68, 0.93; p = 0.004). Among HIV-positive PWID (n = 47), there was no significant association in HIV disease progression in individuals above or below the median level of α4β7 expression (log-rank p = 0.84). In contrast to findings in heterosexual women, higher α4β7 expression does not predict HIV acquisition or disease progression in PWID or MSM. This study was supported in part by the Division of Intramural Research, National Institute of Allergy and Infectious Diseases (NIAID), National Institutes of Health. The study was also supported by extramural grants from NIAID T32AI102623 (E.U.P.), and UM1AI069470.